Be Fearless: 5 Principles for a Life of Breakthroughs and Purpose - Case, Jean; Goodall, Jane 1934- (New York : Simon & Schuster, 2019)
Identifies the five principles that people who have made breakthrough changes in the world have followed, including making a "big bet," taking bold risks, learning from failure, reaching beyond their comfort zone, and letting urgency conquer fear.